ANGIOFIBROMA NASOFARÍNGEO JUVENIL - CASOS CLINICOS - Monteiro, Marta; André, Carla; Santos, Mário; Antunes, Luís; Marta Pimentel, João (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.